Dynamic sex chromosomes in Old World chameleons (Squamata: Chamaeleonidae). (26th February 2018) - Nielsen, S. V.; Banks, J. L.; Diaz, R. E.; Trainor, P. A.; Gamble, T.
Abstract: Much of our current state of knowledge concerning sex chromosome evolution is based on a handful of 'exceptional' taxa with heteromorphic sex chromosomes. However, classifying the sex chromosome systems of additional species lacking easily identifiable, heteromorphic sex chromosomes is indispensable if we wish to fully understand the genesis, degeneration and turnover of vertebrate sex chromosomes. Squamate reptiles (lizards and snakes) are a potential model clade for studying sex chromosome evolution as they exhibit a suite of sex‐determining modes yet most species lack heteromorphic sex chromosomes. Only three (of 203) chameleon species have identified sex chromosome systems (all with female heterogamety, ZZ/ZW). This study uses a recently developed method to identify sex‐specific genetic markers from restriction site‐associated DNA sequence (RADseq) data, which enables the identification of sex chromosome systems in species lacking heteromorphic sex chromosomes. We used RADseq and subsequent PCR validation to identify an XX/XY sex chromosome system in the veiled chameleon ( Chamaeleo calyptratus ), revealing a novel transition in sex chromosome systems within the Chamaeleonidae. The sex‐specific genetic markers identified here will be essential in research focused on sex‐specific, comparative, functional and developmental evolutionary questions, further promoting C. calyptratus' utility as an emerging model organism.